Protective Effect of Dodonaea viscosa (L) Against Lead Acetate Induced Altered Glycoprotein Profiles in Rats - D. Sivanesan; A. V. Veera Thamarai Selvi; R. Bhakyaraj; T. Arunachalam (E-Journal of Chemistry)
The present study was undertaken to examine the inhibitory effect of crude leaves of Dodonaea viscosa (L) on lead acetate induced synthesis of glycoproteins and sialic acid in liver and plasma. Enhanced synthesis of glycoproteins (protein - bound hexose and protein - bound hexosamine) and sialic acid levels were found in liver and plasma of the lead acetate poisoned rats. Administration of crude leaves of D.viscosa (100 mg/100 g body weight P.O.) effectively suppressed the synthesis of glycoproteins and sialic acid in liver and thereby controlling the concentration in plasma. The results suggest that D.viscosa may exert its membrane protection effect by inhibiting the synthesis of glycoproteins and sialic acid induced by lead acetate.